2021
DOI: 10.3346/jkms.2021.36.e192
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes Following Laparoscopic and Open Surgery in Pelvis during Pregnancy: a Nationwide Population-based Study in Korea

Abstract: Background Non-obstetric surgery during pregnancy is associated with adverse obstetric and fetal outcomes. The aim of this study was to investigate the risk of adverse pregnancy outcomes for women who underwent non-obstetric pelvic surgery during pregnancy compared with that of women that did not undergo surgery. Methods Study data from women who gave birth in Korea were collected from the Korea National Health Insurance claims database between 2006 and 2016. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Fourteen studies reported population-based data, 1012,15,22,23,26,29,31,33,35,42,45,50 three studies reported multicenter data 36,39,60 and 43 studies reported single-center data, 13,14,1621,24,25,27,28,30,32,34,37,38,40,41,43,44,4649,5159,6169 and all, expect one small prospective single-center study on 22 women,63 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourteen studies reported population-based data, 1012,15,22,23,26,29,31,33,35,42,45,50 three studies reported multicenter data 36,39,60 and 43 studies reported single-center data, 13,14,1621,24,25,27,28,30,32,34,37,38,40,41,43,44,4649,5159,6169 and all, expect one small prospective single-center study on 22 women,63 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies comparing that aspect, the prevalence was 6.6% (n = 6661) in pregnancies in which non-obstetric surgery was performed and 6.0% (n = 2,328,110) in pregnancies with no surgery, OR 1.1 [1.0-1.2], respectively. 23,26,33,50 In Cho et al 15 study, the prevalence of low birth weight was 5,6% after laparoscopic and 5,8% after open surgery. The prevalence of small for gestational age was 7.0% after laparoscopic surgery (n = 640) and 9.2% after open surgery (n = 521), with an OR of 0.7 [0.5-1.1].…”
Section: Description Of the Studies According To The Fetal And Matern...mentioning
confidence: 92%
See 2 more Smart Citations
“…The reported incidence of ovarian cysts in pregnancy varies from 0.05% to 1.2%; compared with open surgery, laparoscopic surgery adnexal cyst during pregnancy does not increase the risk to mother and fetus. [ 1 2 ] In addition, LESS has better postoperative recovery. However, conventional laparoscopic surgery is safer than LESS.…”
Section: O Bjectivementioning
confidence: 99%